PASTOR CENTER SOLUTION: MODEL KONSELING PASTORAL BAGI WARGA JEMAAT GENERASI Z DAN ALPHA YANG KECANDUAN GAME ONLINE - Ruth Anugrah Olivia; David Eko Setiwan (POIMEN Jurnal Pastoral Konseling, 2022)
Mobile phones have a very high benefit to help humans work, communicate. However, mobile phones can also have the opposite effect if they are used to play games, spending a lot of time doing an activity that is not very useful. If there is no action of an appropriate method of accompaniment in counseling in which the church plays an important role, it will cause an even more complicated problem. The purpose of this research is to reveal a model or method for dealing with children who are addicted to playing online games. ?. The method used in this research is descriptive qualitative. The results of the study show a form of Pastor Center Solution method of pastoral counseling assistance that can be applied to Generation Z and Alpha who are addicted to playing online games, namely the Shepherd who acts as a center for solving Pastoral Counseling problems, fostering parents to become an extension of the hand who can see their children closely. Directly, do a follow-up regarding the development of children who are addicted to online games.